2020
DOI: 10.1142/s0217984920502644
|View full text |Cite
|
Sign up to set email alerts
|

Design for tunable optofluidic optical coupler with large dynamic range

Abstract: A novel scheme for tunable optofluidic optical coupler is proposed by combining directional coupling waveguide structures with microfluidic channel. The normalized optical power at two output ports can be dynamically manipulated by controlling the refractive index of liquid mixture in microfluidic channel. Its optical performance is numerically investigated by employing the beam propagation method (BPM). The simulated results show that the dynamic range of over 45 dB, and optical loss of below 0.06 dB can be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…[ 46 ] These works indicated that, different from the van der Waals‐like fluid, the black hole in the AdS space has only a minimum inversion temperature, without a maximum one. The successive studies in various extended theories of gravity further confirmed these conclusions, [ 47–84 ] and the basic reason is the slight difference between the EoS of the black hole and the van der Waals‐like fluid.…”
Section: Introductionmentioning
confidence: 75%
“…[ 46 ] These works indicated that, different from the van der Waals‐like fluid, the black hole in the AdS space has only a minimum inversion temperature, without a maximum one. The successive studies in various extended theories of gravity further confirmed these conclusions, [ 47–84 ] and the basic reason is the slight difference between the EoS of the black hole and the van der Waals‐like fluid.…”
Section: Introductionmentioning
confidence: 75%